Exploring Consumer Experiences in Toy Selection: A Study on Hot Wheels and Fire Truck - Fani Putri Agustiani; Sayida Khoiratun Nisak; Ahmad Edi Saputra; Alisyah Pitri; Hasna Dewi (Journal of Innovative and Creativity, 2025)
The study purpose was to analyze differences in consumer perceptions of Hot Wheels and Fire Truck toys at Time Toys, WTC Batanghari Mall, Jambi City, with a specific focus on the influence of price and product quality on consumer satisfaction. The study also aimed to identify service elements that most significantly impact purchasing decisions and to provide recommendations for improving competitiveness in the specialty toy retail sector. This research addresses the urgency of understanding the interplay between tangible product attributes and intangible service factors within the context of Indonesian modern retail. Materials and methods. This study adopted a comparative, cross-sectional design involving consumers who had purchased or considered purchasing Hot Wheels or Fire Truck toys in the past six months. A purposive sampling method was used to ensure participants possessed relevant experience and familiarity with both products. Data were collected using structured questionnaires, distributed in-store and online, measuring demographic characteristics, perceptions of product quality and price fairness, and overall satisfaction. Descriptive statistics were applied to summarize general patterns, independent samples t-tests were used to examine differences in perceptions, and multiple regression analysis was conducted to assess the relative influence of price and quality on satisfaction, with a significance threshold of p < 0.05. Results. The findings revealed that while price and product quality significantly influenced purchasing decisions, service quality emerged as a more dominant determinant of consumer satisfaction. Elements such as transaction transparency, accountability, conditional service tailored to situational needs, and equitable treatment without discrimination were highly valued by customers. Additionally, the provision of supportive facilities, flexibility in payment methods, member-exclusive discounts, and short-term product replacement guarantees enhanced the overall shopping experience. Employee motivation, reinforced by managerial guidance and religious values, contributed to consistently high service standards. Conclusions. The study concludes that in specialty toy retail, service quality can outweigh traditional factors like price and product quality in shaping customer satisfaction. The novelty lies in identifying conditional service as a culturally relevant competitive advantage and highlighting the integration of ethical and spiritual values in service delivery. Retailers are advised to integrate pricing and quality strategies with comprehensive management of the shopping experience, combining efficiency with relational depth to sustain customer loyalty and long-term business